Pillar, Speaker, Mother: The Character of Calla in A Jest of God - Relke, Diana M.A. (Studies in Canadian Literature, 1988)
This article is an attempt to redress critics’ neglect of the minor characters in Margaret Laurence’s novels. The character of Calla in A Jest of God is the only character in the novel who is directly connected with all the major themes. She is, symbolically, the protaganist’s (Rachel’s) surrogate mother, enlarging on and concretizing the motherhood theme that runs through much of Laurence’s work. She survives, even thrives, in the stifling world of Manawaka, providing simultaneously an escape and a sort of revisionist moral barometer for Rachel. Calla is associated through overt symbolism with homosexuality, which suggests further escape from the moral confines of the sexually conservative region.